Political Exclusion and Disenfranchisement in the Electoral Systems of India and Israel under International Human Rights Standards - Rahmadani, Firdausi Nuzula; Jumantoro, Tegar Raffi Putra (PT. Riset Press International, 2025)
This study investigates the institutionalization of political exclusion and electoral disenfranchisement in India and Israel, two states that claim adherence to democratic norms while systematically excluding specific populations from political participation. Drawing on a normative legal approach, this paper analyzes how domestic legislation, particularly India's Citizenship Amendment Act (CAA) and National Register of Citizens (NRC), as well as Israel's Nation-State Law, creates legal frameworks that contradict international human rights standards. Using statute, conceptual, and comparative approaches, the research evaluates the extent to which these legal instruments undermine the principles of universal suffrage and non-discrimination as outlined in the ICCPR and UDHR. The findings reveal that both states employ legalistic mechanisms, whether through administrative verification processes or territorial segmentation, to disenfranchise ethnic and religious minorities under the guise of lawful governance. This practice not only erodes the integrity of electoral democracy but also highlights a legitimacy gap between national legal systems and international normative expectations. The study emphasizes the urgency of confronting “authoritarian legalism” in democratic regimes, which often escape international accountability. Although limited by its reliance on secondary data and absence of empirical fieldwork, this paper contributes to the global discourse on electoral justice by exposing how law can be weaponized to suppress political inclusion. Future research should explore the lived impacts of disenfranchisement and assess how international bodies can strengthen enforcement of electoral rights. Ultimately, genuine democracy cannot exist where the right to vote is selectively granted, and legal systems are used to sustain structural exclusion.